Does Metabolic Syndrome Increase Erectile Dysfunction and Lower Urinary Tract Symptoms? - Coban, Soner; Cander, Soner; Altuner, Mehmet Sakir; Keles, Ibrahim; Gul, Ozen Oz (Urology Journal, 2014)
Purpose: To evaluate the impact of metabolic syndrome (MS) on erectile dysfunction (ED) and lower urinary tract symptoms (LUTS). Materials and Methods: We included patients who had presented at the urology outpatients with LUTS or ED complaints and at the endocrinology outpatients for diabetes between May 2012 and April 2013. MS was present in 50 of the 107 patients (42.7%). The blood pressure, fasting blood sugar, serum lipid profile, triglyceride, total cholesterol, body mass index (BMI) and total prostate specific antigen (PSA) values were recorded. The international prostate symptom score (IPSS), quality of life score and international erectile function index (IIEF-5) values were determined for the patients. All patients also underwent uroflowmetry together with prostate volume and residual urine volume measurement. Results: There was a significant negative correlation between the IPSS and IIEF scores of the patients (P < .001, r = -0.42). There was no significant difference regarding IPSS scores between patients with and without MS (P = .6), while the IIEF-5 scores were significantly lower in the MS group (P = .03). Conclusion: We found that metabolic syndrome did not significantly affect LUTS but could significantly contribute to ED. We therefore feel patients presenting with ED complaints should also be carefully evaluated for MS.